Faktor-Faktor yang Berhubungan dengan Dinamika dan Keberhasilan Bumdes dalam Mengembangkan Perekonomian Masyarakat Desa di Kabupaten Pesawaran - Reni Meilana; Helvi Yanfika; Tubagus Hasanuddin (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
Rural poverty in Indonesia receives excellent attention. Therefore, many poverty reduction programs have been created. The government has made a Village-Owned Enterprises (BUMDes) program to improve people's welfare. This study aims to determine the socioeconomic factors related to the dynamics and success of BUMDes in developing the economy of rural communities. The variables in this study are the amount of capital, motivation, leadership, availability of facilities and infrastructure, village government support, the number of business types, and the dynamics of BUMDes on the success of BUMDes The research was conducted from September to October 2022. Respondents in this study totaled 60 people consisting of administrators and the village community. Data collection was carried out through interview techniques with questionnaires. Analysis of the data used nonparametric statistics with the Spearman Rank correlation test. The results of this study indicate that the amount of capital, motivation, leadership, and availability of infrastructure are related to BUMDes dynamics and success. Still, village government support and the number of types of businesses are not related to BUMDes dynamics and success.